2020
DOI: 10.4254/wjh.v12.i11.976
|View full text |Cite|
|
Sign up to set email alerts
|

Screening and identification of bioactive compounds from citrus against non-structural protein 3 protease of hepatitis C virus genotype 3a by fluorescence resonance energy transfer assay and mass spectrometry

Abstract: BACKGROUND Hepatitis C virus genotype 3a (HCV G3a) is highly prevalent in Pakistan. Due to the elevated cost of available Food and Drug Administration-approved drugs against HCV, medicinal natural products of potent antiviral activity should be screened for the cost-effective treatment of the disease. Furthermore, from natural products, active compounds against vital HCV proteins like non-structural protein 3 (NS3) protease could be identified to prevent viral proliferation in the host. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…During transfection of the mcherry-HCV protease and the cpGFP-CS-Nb39 protein components, we added BILN-2061 in a range of concentrations to the HEK293T cells and then fixed and imaged 24 h later. Image analysis and quantification showed that the IC 50 value of the SPOTon protease assay was 151 nM (Figure D), which is 3× higher than an IC 50 value reported in a fluorescence resonance energy transfer (FRET)-based in vitro assay . This is likely because the inhibitor needs to be added right after transfection and incubated for 24 h before imaging to inhibit HCV protease activity throughout the experiment.…”
Section: Resultsmentioning
confidence: 77%
“…During transfection of the mcherry-HCV protease and the cpGFP-CS-Nb39 protein components, we added BILN-2061 in a range of concentrations to the HEK293T cells and then fixed and imaged 24 h later. Image analysis and quantification showed that the IC 50 value of the SPOTon protease assay was 151 nM (Figure D), which is 3× higher than an IC 50 value reported in a fluorescence resonance energy transfer (FRET)-based in vitro assay . This is likely because the inhibitor needs to be added right after transfection and incubated for 24 h before imaging to inhibit HCV protease activity throughout the experiment.…”
Section: Resultsmentioning
confidence: 77%
“…This significant variation in the activity assay has altered the downstream inhibitory activities of extracts and natural products. Regrettably, this situation has forced us to retract our paper[ 2 ] to conduct more experimentation and make the major correction in data, before we can consider its rewriting and publication.…”
Section: To the Editormentioning
confidence: 99%